Bisphenols and Risk of Breast Cancer: A Narrative Review of the Impact of Diet and Bioactive Food Components - Stillwater, Barbara J.; Bull, Ashleigh C.; Romagnolo, Donato F.; Neumayer, Leigh A.; Donovan, Micah G.; Selmin, Ornella I. (Frontiers in Nutrition, 2020)
Data from preclinical studies suggest a link between increased risk of breast cancer and exposure to bisphenols at doses below what the Federal Drug and Administration (FDA) considers as safe for consumption. Bisphenols exert estrogenic effects and are found in canned and plastic wrapped foods, food packaging, and plasticware. Mechanistically, bisphenols bind to the estrogen receptor (ER) and activate the expression of genes associated with cell proliferation and breast cancer. In this paper, we present a narrative literature review addressing bisphenol A and chemical analogs including bisphenol AF, bisphenol F, and bisphenol S selected as prototype xenoestrogens; then, we discuss biological mechanisms of action of these bisphenols in breast cells and potential impact of exposure at different stages of development (i.e. perinatal, peripubertal, and adult). Finally, we summarize studies detailing interactions, both preventative and promoting, of bisphenols with food components on breast cancer risk. We conclude the review with a discussion of current controversies in interpretation of the above research and future areas for investigation, including the impact of bisphenols and food components on breast tumor risk.